2009
DOI: 10.1101/sqb.2009.74.023
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Virus Evolution: The Relationship between Genetic Robustness and Evolvability of Thermotolerance

Abstract: As a naturalist, Charles Darwin was understandably fascinated by the species diversity visible in the natural world. However, he understood little of the invisible realm of genes-the units of inheritance that are passed across generations and contribute to the phenotypic variation evident in biological populations. Yet Darwin showed remarkable insight when formulating his ideas on evolution via natural selection, as a process whereby the environment determines which variants in a population are favored to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…We found no evidence that the robust populations were pre-adapted to be more thermotolerant as there was no survival difference between robust and brittle populations at 42.5 and 45°C. However, these measurements were taken for the entire population and there may have been individual clones, which were more thermotolerant (Ogbunugafor et al, 2009). Future work could test if our evolvability results are generalizable to other traits.…”
Section: Discussionmentioning
confidence: 99%
“…We found no evidence that the robust populations were pre-adapted to be more thermotolerant as there was no survival difference between robust and brittle populations at 42.5 and 45°C. However, these measurements were taken for the entire population and there may have been individual clones, which were more thermotolerant (Ogbunugafor et al, 2009). Future work could test if our evolvability results are generalizable to other traits.…”
Section: Discussionmentioning
confidence: 99%
“…However, (i) there is little empirical evidence that genetic canalization can actually evolve in real populations (in particular in sexual species) [28], (ii) quantitative characters are far from being completely canalized, as evidenced by the prevalence of monogenic diseases or lethal mutations, and by the high level of genetic variance in most natural populations [29], and (iii) little is known about how canalization translates into observable properties from real genetic systems. In this paper, we aim to challenge theoretically the limits and the prediction power of the “canalizing gene networks” theory.…”
Section: Introductionmentioning
confidence: 99%
“…Also, recent work with bacteriophages has shown that mutational robustness increases the ability to adapt to stressful conditions such as high temperatures (McBride et al. , 2008; Ogbunugafor et al. , 2009).…”
Section: Introductionmentioning
confidence: 99%